Pemanfaatan Alat Musik Tradisional Suku Mbojo Berbasis Model Project Based Learning (PjBL) pada Materi Gelombang Bunyi untuk Meningkatkan Literasi Sains - Febiyanti Ansumarwaty (Mataram University, 2026)
This study aims to analyze the practicality of physics learning based on the Project Based Learning (PjBL) model integrated with traditional musical instruments of the Mbojo Tribe on sound wave material as an effort to support contextual learning and develop students’ scientific literacy. This research employed a Research and Development (R&D) method using the 4D model, consisting of define, design, develop, and disseminate stages, although the study was limited to the develop stage. The subjects of the study were students of class XI MIPA at SMAN 1 Monta. Data were collected through learning implementation observation sheets and student response questionnaires. The data were analyzed descriptively using quantitative methods by calculating the practicality percentage. The results showed that the implementation of learning obtained a percentage of 94.56%, categorized as very practical. Meanwhile, student responses obtained a percentage of 89.54%, also categorized as very practical. The learning process was carried out through six stages of PjBL integrated with scientific literacy indicators, namely explaining scientific phenomena, identifying scientific issues, and using scientific evidence. Therefore, PjBL-based learning utilizing traditional musical instruments of the Mbojo Tribe was declared highly practical.